Desempenho de mecanismos de corte dos resíduos culturais e abertura de sulco para a semeadura direta - Francetto, Tiago Rodrigo (2014)
The objective of this work was to evaluate the tractor/toolholder operating performance equipped with different configurations of the cutting elements of crop residues and soil breakers, depending on the speed. This was done in a farm located in the municipality of Santa Maria (Rio Grande do Sul). The experimental area's soil was classified as Red Alfisol and loamy sand texture. The experiment consisted of 24 treatment combinations in a factorial scheme 2x3x4. These were composed by the interaction of mechanisms factors of furrow opening (furrow opener fixed and rotary), cutting crop residues (without hard, smooth and fluted disc) and travel speeds (1.11, 1.67, 2.22 and 2.78 m s-1). Farm's performance data tractors were acquired with the use of electronic instrumentation. The associations between furrow opener and disc showed better performance at speeds of 1.11 and 1.67 m s-1 for required lesser traction force, power in the bar and fuel consumption. Furthermore, the cutting discs use allowed a reduction of increased demand traction force when the speed went from 1.11 to 2.78 m s-1. The furrow shanks required greater demand traction than mismatched drives and both, when combined with the cutting discs, had increased their demand with greater significance for association with fluted disc. The proportionality of this variable was proved with the hourly consumption and the splipping. The soil mobilization was not influenced by the speed, being higher with the use of the shank, and among the combinations with disc, it was superior to fluted.